Does institutional investor influence information technology investment decisions and corporate performance? - Abdelkader Alghorbany; Abdulmalik Salau Olarinoye; Moses Elaigwu; Ayoib Che-Ahmad (Cogent Business & Management, 2024)
This paper examines the role of institutional investors foreign-owned firms and government-linked companies, in improving firm performance through the channel of IT investment decision. The data sample comprises information collected from the annual reports of 231 companies listed on Bursa Malaysia, spanning the years 2010 to 2019. This study concludes, on the basis of the Generalized Method of Moments (GMM) dynamic model, which mitigates the endogeneity issue linked to the equity multiple value model, that institutional ownership moderates the relationship between IT investment and firm performance in a positive direction. The results of the study shed light on the capacity of institutional investors to allay apprehensions regarding agency problems that arise from the rent-seeking conduct of managers. The implications of this finding are both theoretical and practical, given that IT expenditures continue to constitute a substantial proportion of the capital budgets of organisations. However, several studies indicate that there is no direct relationship between firm IT investment levels and firm performance. This study contributes to the body of knowledge by examining the influence of institutional investors on IT investment decisions. It does so by integrating agency theory, which explains performance shortfalls, and corporate governance, which oversees and controls managers' inappropriate investment choices, thereby illuminating the antecedents of IT investment decisions. The present investigation would furnish significant insights for stakeholders, investors, and the general public, thereby augmenting their understanding of the pivotal significance of institutional ownership and guaranteeing that investments in IT are adequately regulated.
Keywords: 650; IT investment; government-linked companies; foreign-owned firms; equity value multiple